2009
DOI: 10.1007/s00268-009-0331-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Long‐Term Survival in Patients with Esophageal Cancer Who Underwent Esophagectomy After Chemoradiotherapy

Abstract: This study reveals that postoperative morbidity affects not only the perioperative mortality but also the long-term survival of patients with ESCC who undergo salvage esophagectomy after definitive CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 37 publications
2
80
0
4
Order By: Relevance
“…Eleven studies were identified in the initial literature search to meet inclusion criteria ( Figure 1) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). After screening, one further publication (23), was excluded as this institution published their outcomes in a follow-up publication, which was included in the analysis (16).…”
Section: Study and Patient Demographicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies were identified in the initial literature search to meet inclusion criteria ( Figure 1) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). After screening, one further publication (23), was excluded as this institution published their outcomes in a follow-up publication, which was included in the analysis (16).…”
Section: Study and Patient Demographicsmentioning
confidence: 99%
“…After screening, one further publication (23), was excluded as this institution published their outcomes in a follow-up publication, which was included in the analysis (16). Therefore, ten comparative studies were included in this pooled final analysis (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In total 1,906 patients were included, 563 in the salvage group and 1,343 in the NCRS group.…”
Section: Study and Patient Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of postoperative mortality was assessed in a considerable number of studies [61][62][63][64][65], fewer assessed in-hospital mortality, and 30-day mortality was determined in two studies [66]. Values were higher in patients who were treated with salvage esophagectomy after deinitive chemoradiotherapy (23 patients-9.50%) than in patients who treated with planned esophagectomy after neoadjuvant chemoradiotherapy (29 patients-4.07%).…”
Section: Postoperative Outcomementioning
confidence: 99%